Pengembangan Model Prediksi Kinerja Proyek Menggunakan Earned Value Management Berbasis Data Progres Mingguan - Firdausi, Annisa Azhar; Ristanto, Iwan; Burhanudin, Faisal (Sultra Civil Engineering Journal (SCiEJ), 2025)
Construction projects are inherently complex due to the involvement of human resources, materials, equipment, costs, and schedules. In Indonesia, project delays and cost overruns remain common issues, often caused by weak monitoring and control mechanisms. Conventional reporting methods, which rely mainly on progress percentages or S-curves, are limited because they do not provide integrated information on cost, time, and performance. This study develops a project performance prediction model using Earned Value Management (EVM) based on weekly progress data, with a case study on the construction of the LPPM & BPMI Building at Veteran Bangun Nusantara University. The research applies an applied case study approach, utilizing project documents and weekly progress reports as the primary data. Indicators such as Planned Value (PV), Earned Value (EV), Schedule Variance (SV), and Schedule Performance Index (SPI) were calculated for weeks 1–13. The analysis shows that while the project was initially ahead of schedule (positive SV and SPI > 1 in weeks 1–5), performance declined significantly after week 6. At week 13, the SV turned negative with an increasing gap between planned and actual progress, while the SPI dropped to 0.44, indicating serious schedule inefficiency. Forecasting results using EVM predict that the project, initially planned for completion in 25 weeks, will require 41 weeks, resulting in a delay of approximately 16 weeks.